Republic of Poland : Financial Sector Assessment Program-Technical Note-Competition and Performance in the Polish Second Pillar. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note for the Republic of Poland on competition and performance explains the Polish pension system and domestic capital market. Competition policies may need to be reviewed, in particular the combination of measures to maintain small pension funds operating while imposing strict caps on fees. If the government decides to continue pursuing policy of promoting competition in returns while reducing fees further, it may need to consider more structural changes in the second pillar, along the lines of the Swedish model.